2020
DOI: 10.3389/fsoc.2020.590935
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Loneliness Among Older Adults

Abstract: The COVID-19 pandemic has created a pattern of everyday physical distancing worldwide, particularly for adults aged 65+. Such distancing can evoke subjective feelings of loneliness among older adults, but how this pandemic has influenced that loneliness is not yet known. This study, therefore, explored the association between subjective loneliness and different time phases of the COVID-19 pandemic to explain the pandemic's impact on loneliness among older adults. The analysis employed a sample of 1,990 communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 15 publications
10
72
1
8
Order By: Relevance
“…Positive SPA decreased and negative SPA increased between the first and second subgroups, but positive SPA slightly increased and negative SPA decreased, as a possible “normalization” of SPA, after the Federal Council called for easing the official COVID-related restrictions. Other recent studies have also found these up-and-down movements for loneliness among older adults, indicating that loneliness increased during the first weeks of the COVID-19 lockdown and decreased thereafter ( Buecker et al, 2020 ; Höglinger et al, 2020 ; Seifert & Hassler, 2020 ). However, the present data collection ended on May 5, 2020, and, therefore, further research is needed to evaluate future developments.…”
Section: Discussionmentioning
confidence: 70%
“…Positive SPA decreased and negative SPA increased between the first and second subgroups, but positive SPA slightly increased and negative SPA decreased, as a possible “normalization” of SPA, after the Federal Council called for easing the official COVID-related restrictions. Other recent studies have also found these up-and-down movements for loneliness among older adults, indicating that loneliness increased during the first weeks of the COVID-19 lockdown and decreased thereafter ( Buecker et al, 2020 ; Höglinger et al, 2020 ; Seifert & Hassler, 2020 ). However, the present data collection ended on May 5, 2020, and, therefore, further research is needed to evaluate future developments.…”
Section: Discussionmentioning
confidence: 70%
“…For an exception, Buecker, Horstmann, et al (2020) found that, on average, loneliness slightly increased during the first two weeks of the COVID-19 pandemic but decreased thereafter. A recent study from Switzerland (Seifert & Hassler, 2020) found that loneliness increased after the Swiss government recommended contact restrictions and slightly decreased after these restrictions were eased. If one assumes that loneliness changes during the Covid-19 pandemic are non-linear, studies examining changes in loneliness at different time points will necessarily come to different conclusions.…”
Section: Heterogeneity In the Study Designs And Resultsmentioning
confidence: 99%
“… 8 In Switzerland, a study conducted in adults over 65 years old to determine the impact of COVID-19 on loneliness, pointed out that female sex, not having children, living alone, having low economic income and being dissatisfied with neighbors can be predictors for the appearance of loneliness. 7 Cultural factors and differences in living conditions according to countries are important for explaining the differences in the prevalence of loneliness. This trend tends to be higher in central and southern Europe than in northern Europe; at the same time, there are differences between Western and Eastern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is accompanied by fear, uncertainty, economic tension and other stressors, which are detrimental to mental health. 7 - 11 …”
Section: Introductionmentioning
confidence: 99%